2020
DOI: 10.1038/s41598-020-71675-7
|View full text |Cite
|
Sign up to set email alerts
|

Molecular mechanisms underlying AMH elevation in hyperoestrogenic states in males

Abstract: Anti-Müllerian hormone (AMH) is secreted by Sertoli cells of the testes from early fetal life until puberty, when it is downregulated by androgens. In conditions like complete androgen insensitivity syndrome (CAIS), AMH downregulation does not occur and AMH increases at puberty, due in part to follicle-stimulating hormone (FSH) effect. However, other conditions like Peutz-Jeghers syndrome (PJS), characterised by low FSH, also have increased AMH. Because both CAIS and PJS may present as hyperoestrogenic states,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
23
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 22 publications
(25 citation statements)
references
References 106 publications
2
23
0
Order By: Relevance
“…Furthermore (Figure 4a), the hormone assay data revealed hypogonadotropic hypogonadism in Tg mice, with low plasma FSH, LH, and testosterone levels and an elevated plasma AMH level. This situation has been reported in other disorders, such as delayed puberty (i.e., childhood levels or hormones) and central hypogonadism (high AMH levels for age) [29][30][31]. AMH is secreted by prepubertal Sertoli cells in response to Furthermore (Figure 4a), the hormone assay data revealed hypogonadotropic hypogonadism in Tg mice, with low plasma FSH, LH, and testosterone levels and an elevated plasma AMH level.…”
Section: Discussionsupporting
confidence: 72%
See 1 more Smart Citation
“…Furthermore (Figure 4a), the hormone assay data revealed hypogonadotropic hypogonadism in Tg mice, with low plasma FSH, LH, and testosterone levels and an elevated plasma AMH level. This situation has been reported in other disorders, such as delayed puberty (i.e., childhood levels or hormones) and central hypogonadism (high AMH levels for age) [29][30][31]. AMH is secreted by prepubertal Sertoli cells in response to Furthermore (Figure 4a), the hormone assay data revealed hypogonadotropic hypogonadism in Tg mice, with low plasma FSH, LH, and testosterone levels and an elevated plasma AMH level.…”
Section: Discussionsupporting
confidence: 72%
“…AMH is secreted by prepubertal Sertoli cells in response to Furthermore (Figure 4a), the hormone assay data revealed hypogonadotropic hypogonadism in Tg mice, with low plasma FSH, LH, and testosterone levels and an elevated plasma AMH level. This situation has been reported in other disorders, such as delayed puberty (i.e., childhood levels or hormones) and central hypogonadism (high AMH levels for age) [29][30][31]. AMH is secreted by prepubertal Sertoli cells in response to FSH, and AMH levels are elevated during fetal life and throughout puberty.…”
Section: Discussionmentioning
confidence: 57%
“…In the male fetus, AMH was secreted by Sertoli cells of the testes from early fetal life, which remained a high level and thus induced physiological involution of the paramesonephric Müllerian ducts. Although the regression of the paramesonephric Müllerian ducts was complicated early in gestation, the production process of AMH by Sertoli cells continued until adulthood [ 42 ]. In the female fetus, the AMH was secreted by granulosa cells of the ovarian follicles from 36 weeks of gestation until menopause, whose expression peak was in preantral follicles and small antral follicles.…”
Section: Discussionmentioning
confidence: 99%
“…In androgen insensitivity syndrome, however, the relatively high gonadotropins and lack of a functional androgen receptor cause AMH levels to be inappropriately high for the degree of testosterone in the serum ( 56 ). Recent studies indicate that the hyperestrogenic state in complete AIS may also play a role in AMH elevation ( 58 ). A study of the testosterone response to human chorionic gonadotropin (hCG) stimulation in prepubertal patients with 46,XY DSD found that a normal serum AMH had a positive predictive value of 84% for a normal post-hCG testosterone level, but a low AMH was not useful in predicting a suboptimal testosterone response ( 59 ).…”
Section: Clinical Utility Of Amhmentioning
confidence: 99%